Design and implementation of a virtual synchronous generator-based microgrid system - Zhang, Ruiqi (2017)
With the development of technology and economy, the demand of electricity in modern society becomes increasingly higher. Hence the penetration of distributed/renewable-energy generation is increasing in power system. However, common control strategies for distributed generation will have negative effects on the system stability. The novel strategy to control the grid-connected inverters using PWM technique which is known as virtual synchronous generators (SGs) can cope with this problem. In this project, a virtual synchronous generator (VSG) – based microgrid system is proposed. Firstly, the mathematical models of conventional SGs and the VSG system are developed. After that, the controller consists of a PI controller and a repetitive controller for voltage regulation based on the mathematical model is designed in detail. At last, both simulation and experiment results are discussed and analyzed to verify the function of the proposed system. Both the simulation and experimental results prove that the developed system together with the controller has good performance on voltage regulation.